THE EFFECTIVENESS OF THE HALODOC IN BUILDING HEALTH AWARENESS AT AL AZHAR 12 ISLAMIC HIGH SCHOOL - Anggriani; Jeanny Maria Fatimah; Muh Akbar (Sociae Polites, 2023)
The objectives of this study are: (1) To determine the intensity of the use of online mass media (Halodoc website) among students of Al Azhar 12 Islamic High School in Makassar; (2) To understand how students of Al Azhar 12 Islamic High School in Makassar pay attention to a healthy lifestyle; (3) To assess the effectiveness of online mass media (Halodoc Health Website) in building Health Awareness among students of Al Azhar 12 Islamic High School in Makassar. This research employs a quantitative research method with an associative correlational approach. Data collection techniques include questionnaires and literature studies. The population of this study comprises students from Al Azhar 12 Islamic High School in Makassar. The research sample is determined through probability sampling. The total population of the study is 96 individuals, and using Taro Yamene's formula, the sample size is determined to be 77 individuals. The collected data are processed using IBM SPSS Version 28.0.1.1 (14). The results of this study indicate that (1) the level of intensity in the use of online mass media (Halodoc Health Website) among students of Al Azhar 12 Islamic High School in Makassar falls under the category of "Very High." (2) The attention of students from Al Azhar 12 Islamic High School in Makassar to a healthy lifestyle, including consuming nutritious and balanced meals, getting sufficient rest, managing stress effectively, and engaging in regular exercise, is categorized as "High." (3) The correlation analysis results show a significant effectiveness between the use of online mass media (Halodoc Health Website) in building Health Awareness among students of Al Azhar 12 Islamic High School in Makassar. Keywords: Halodoc Health Website, Health Awareness